An Activated Carbon-Based Water Filter Innovation from Oyster Mushroom Baglog Waste for Clean Water Solutions in Payakabung Village, Ogan Ilir, South Sumatera - Puspitahati, Puspitahati; Husein, Saddam; Purnamasari, Amrina; Pradani, Aulia Farah; Heriyanto, Abdul Roni (Program Pascasarjana Universitas Sriwijaya, 2025)
Research is an innovation in utilizing oyster mushroom baglog waste as a material in water filtration, which is being researched and applied to the community. Water samples were 3 samples for each 3 locations taken form two villages, namely: 1) water used for oyster mushroom cultivation in Payakabung Village (S1), 2) water used for household needs in Payakabung Village (S2), and 3) The Indralaya Combined Cycle Power Plant uses water from the Kelekar River, Tanjung Seteko Village (S3). This study was conducted with three treatments and two replications at each water sample location, as follows: Oyster mushroom baglog waste briquette composition: 10% (A), 20% (B) and 30% (C). The results showed that. The filtration can increase the pH value from acidic to neutral value and decrease Fe concentration. However, several water quality parameters (TDS, Mn, NO2-N, NO3-N, Cl2, Cd, Pb, F, BOD , COD, total coliform and Escherichia coli) show varying trends but are still in accordance with the quality standards of existing regulations. Technology validation to the community showed that most of participant understood and 100% considered that the system useful as solution for their water problems.